Literature practices in high school: a (re)think about literary reading and reader formation (Olhar de Professor, 2024)
Reading is a fundamental condition for the production of knowledge and is configured in a context mediated by language as a form of human interaction. This study aimed to reflect on practices to encourage literary reading in the school context, as well as reader training based on the novel genre. This is qualitative research, with characteristics of action research, developed through the Reception Method (BORDINI; AGUIAR 1988), in the second semester of 2022. Such practices were experienced through the literary pizza project with students in the 1st year of Education Medium, from the Ulisses Guimarães State School, located in the municipality of Campo Verde-MT. Brazil (1998), Aguiar (2001), Lajolo (1997), Freire (1998), among others, were used as theoretical support. It is concluded that literary reading promotes situations of appreciation, dialogue and interaction between the reader and the author, when mediated by the literary text, as well as strengthening young people's contact with literature.
Keywords: Teaching.; Romance Genre; Reception Method